2016
DOI: 10.1007/s00253-016-7538-0
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter waves or extremely high frequency electromagnetic fields in the environment: what are their effects on bacteria?

Abstract: Millimeter waves (MMW) or electromagnetic fields of extremely high frequencies at low intensity is a new environmental factor, the level of which is increased as technology advance. It is of interest that bacteria and other cells might communicate with each other by electromagnetic field of sub-extremely high frequency range. These MMW affected Escherichia coli and many other bacteria, mainly depressing their growth and changing properties and activity. These effects were non-thermal and depended on different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 66 publications
2
20
0
1
Order By: Relevance
“…Moreover, there are probably some compensatory cellular mechanisms which might prevent the increase in the EMF stress effects on bacteria (Soghomonyan et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Moreover, there are probably some compensatory cellular mechanisms which might prevent the increase in the EMF stress effects on bacteria (Soghomonyan et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…) and others, especially lactic acid bacteria (Soghomonyan and Trchounian ) at different frequencies (Soghomonyan et al . ). Note that Enterococci belong to lactic acid bacteria (Fisher and Phillips ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, a review has highlighted the possibility of cellular interactions with RF, including cell plasma membrane, genome, and the presence of water, which may the cause of the diversions from normal activities of various bacteria strains. This was articulated in the highlights of previous research, which observed altered ionic transport processes and enzymatic activity in the plasma membranes of bacteria when exposed to certain frequencies between 50–73 GHz [16]. The navigation of honeybees were said to be affected due to the magnetite structures in the bee, acting as a natural compass interfered by telecommunication antenna radiations [8].…”
Section: Introductionmentioning
confidence: 99%